Systematic engineering of Pichia pastoris for high-level production of recombinant human granulocyte-macrophage colony-stimulating factor - Zhenzhen Cheng; Keyu Gong; Yuchao Song; Zhenchang Guo; Wenjun Guan (Bioresource Technology, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Engineering a 2-methylimidazole framework nanozyme for efficient oxidation of lactose to lactobionic acid under mild conditions - Donghui Xie; Yanna Jiao; Shaoyi Yu; Jia Tu; Yunhui Cheng; Xiaohong He; Daichen Mu; Keyu Xing; Zhou Xu (Journal of Environmental Chemical Engineering, 2026)

Effects of oxygen-fuel velocity ratio on soot formation and flame structure in CH4-CO2-O2 inverse diffusion flames - Teng Hu; Keyu Cheng; Huajie Lyu; Jun Wan; William L. Roberts; Chenghang Zheng; Peng Liu; Xiang Gao (Fuel, 2026)

Exogenous melatonin regulates hormone metabolism involved in delaying the ripening process in cherry tomato fruit during storage - Hang Zhang; Yue Wang; Jianhui Cheng; Wenbo Lei; Keyu Xu; Lilai Yin; Chen Huan; Shuling Shen; Lanying Yao; Xiaolin Zheng (Postharvest Biology and Technology, 2025)

Evaluating Gas Saturation in Unconventional Gas Reservoirs Using Acoustic Logs: A Case Study of the Baiyun Depression in the Northern South China Sea - Jiangbo Shu; Changchun Zou; Cheng Peng; Liang Xiao; Keyu Qiao; Xixi Lan; Wei Shen; Yuanyuan Zhang; Hongjie Zhang (Journal of Marine Science and Engineering, 2025)
Shallow gas is an unconventional natural gas resource with great potential and has received growing attention recently. Accurate estimation of gas saturation is crucial for reserves assessments and for development program formulations. However, such reservoirs are characterized by weak diagenesis, a high clay content, and low resistivity. These properties pose significant challenges for saturation evaluations. To address the challenge of insufficient accuracy in evaluating the saturation of gas-bearing reservoirs, we propose an acoustic-based saturation evaluation method. In this study, a shallow unconsolidated rock physics model is first constructed to investigate the effect of variations in the gas saturation on elastic wave velocities. The model especially considers the patchy distribution of fluids within pores. In addition, we propose an iterative algorithm based on the updated relationship between porosity and gas saturation by introducing a correction term for the saturation to the density porosity, and successfully apply it to the logging data collected from the shallow gas reservoirs in the Pearl River Mouth Basin of the South China Sea. It is evident from the results that the saturation derived from the array acoustic logs is comparable to that obtained from the resistivity logs, with a mean absolute error of less than 6%. Additionally, it is also consistent with the drill stem test (DST) data, which further verifies the validity and reliability of this method. This study provides a novel non-electrical method for estimating the saturation of shallow gas reservoirs, which is essential to promote the evaluation of unconsolidated sandstone gas reservoirs.

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Oxygen vacancies and Li+ pre-embedding for magnesium storage in Anatase TiO2 toward magnesium/lithium hybrid batteries - Haofei Du; Xueyang Hou; Fan Cheng; Yifan Liu; Zhao Fang; Keyu Xie; Ling Zhang (Chemical Engineering Journal, 2025)

Sensitive lateral flow immunoassay enabled by signal amplification strategy with high active oxidase-like nanozymes - Jie Zhu; Yunhui Cheng; Xufeng Wang; Hao Wu; Ye Jiao; Keyu Xing; Li Yao; Pei Jia; Zhou Xu (Food Bioscience, 2025)

Joint optimization of AoI and energy for AUV-assisted data collection in underwater acoustic sensor networks - Weinan Cao; Keyu Chen; En Cheng (Frontiers in Marine Science, 2025)
Underwater data collection is a key component of ocean observation systems, providing reliable data provenance through sensor networks deployed across diverse marine environments. Timely and energy-efficient data collection mechanisms are critical for ensuring the continuity and integrity of the collected data. For the sake of jointly optimizing the age of information (AoI) and energy consumption, we propose a multi-autonomous underwater vehicle (AUV)-assisted underwater data collection scheme in this paper. The optimization problem is formulated as a mixed integer linear programming (MILP) problem, which is non-deterministic polynomial (NP)-hard. In order to address the problem efficiently, we propose a two-stage method. First, considering the balance of energy consumption and the limitation of sensor communication ranges, we design a cluster-based AUV scheduling data transmission protocol to find a series of hovering points at which the AUVs hover to receive data and schedule data transmissions between the AUVs and sensors. Based on that, a combined heuristic algorithm is proposed to plan AUVs’ trajectories so that the data collection task can be completed properly with a low cost. Simulation results show that the proposed algorithm outperforms three benchmark algorithms in terms of average AoI and collection utility. Specifically, the freshness of information and the collection utility improved by 10.23% and 33.36% on average, respectively. Additionally, the energy consumption of sensor nodes is more balanced, and the network lifetime is extended.

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

Whether to continue combining carbapenems to treat carbapenem-resistant Acinetobacter baumannii nosocomial pneumonia in critically ill patients: a retrospective efficacy and safety analysis - Cheng Shiqi; Wang Chuhui; Zhang Yijing; Qiu Yulan; Chen Jiaojiao; Chen Keyu; Shi Qindong; Zeng Xiaoyan; Dong Yalin (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Impact of landform on Spatial-Temporal distribution and Scenario-Based prediction of carbon stocks in arid Regions: A Case study of Xinjiang - Keyu Song; Weiming Cheng; Baixue Wang; Hua Xu (CATENA, 2025)

Isolation of a facultative methanotroph Methylocystis iwaonis SD4 from rice rhizosphere and establishment of rapid genetic tools for it - Yinghui Wang; Yuying Wang; Keyu Zhou; Haili Zhang; Minggen Cheng; Baozhan Wang; Xin Yan (Biotechnology Letters, 2024)

A novel magnetic resonance tuning-magnetic relaxation switching sensor based on Gd-MOF/USPIO assembly for sensitive and convenient aflatoxin B1 detection - Shiqin Dai; Keyu Xing; Yanna Jiao; Shaoyi Yu; Xingyu Yang; Li Yao; Pei Jia; Yunhui Cheng; Zhou Xu (Food Chemistry, 2024)

Effects of natural extract from medicinal herbs on broilers experimentally infected with Eimeria tenella - Yuanyuan Jiang; Yujuan Zeng; Keyu Chen; Haoran Cheng; Songjiang Dai; Xuexue Deng; Long Wang; Jinqiu Liao; Ruiwu Yang; Li Zhang (Veterinary Parasitology, 2024)

A stronger association of mental disorders with smaller particulate matter and a modifying effect of air temperature - Keyu Wu; Junwen Tao; Qiyue Wu; Hong Su; Cunrui Huang; Qingrong Xia; Cuizhen Zhu; Jing Wei; Min Yang; Junwei Yan; Jian Cheng (Environmental Pollution, 2024)

Seasonal peak and the role of local weather in schizophrenia occurrence: A global analysis of epidemiological evidence - Jihong Hu; Yufan Feng; Hong Su; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Keyu Wu; Mohammad Zahid Hossain; Yunquan Zhang; Kejia Hu; et al. (Science of The Total Environment, 2023)

Where does floating Sargassum in the East China Sea come from? - Lin Qi; Peng Cheng; Menghua Wang; Chuanmin Hu; Yuyuan Xie; Keyu Mao (Harmful Algae, 2023)

Target-triggered Fe3O4@NPC-UCNPs assembly for photoactivatable biosensing of Aflatoxin B1 - Zhou Xu; Shaoyi Yu; Xinyi Xie; Qingxia Li; Li Ding; Maolong Chen; Jia Tu; Keyu Xing; Yunhui Cheng (Chemical Engineering Journal, 2023)

A systematic review and meta-analysis of air pollution and angina pectoris attacks: identification of hazardous pollutant, short-term effect, and vulnerable population - Min Yang; Keyu Wu; Qiyue Wu; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Junwen Tao; Hao Zheng; Mohammad Zahid Hossain; Wenyi Zhang; Ning Wang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Abnormal ambient temperature change increases the risk of out-of-hospital cardiac arrest: A systematic review and meta-analysis of exposure types, risk, and vulnerable populations - Qiyue Wu; Min Yang; Keyu Wu; Hong Su; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Thi Anh Thu Dang; Mohammad Zahid Hossain; et al. (Science of The Total Environment, 2023)

Recognition of behavior state of Penaeus vannamei based on passive acoustic technology - Maochun Wei; Keyu Chen; Yating Lin; En Cheng (Frontiers in Marine Science, 2022)
Underwater signal processing based on passive acoustic technology has carried out a lot of research on the behavioral sound of underwater creatures and the protection of marine resources, which proves the feasibility of passive acoustic technology for long-term and non-destructive monitoring of underwater biological sound production. However, at present, most relevant research focuses on fish but little research on shrimp. At the same time, as the main economic breeding industry, Penaeus vannamei has a backward industrial structure, in which the level of intelligence needs to be improved. In this paper, the acoustic signals generated by different physiological behaviors of P. vannamei are collected based on passive acoustic technology. Their different behaviors are finally classified and identified through feature extraction and analysis. Meanwhile, the characteristic non-parametric ANOVA is carried out to explore the relationship between the acoustic signals and the behavior state of P. vannamei to achieve the purpose of real-time monitoring of the behavior state of P. vannamei . The experimental results show that linear prediction cepstrum coefficient (LPCC) and Mel-frequency cepstrum coefficient (MFCC) characteristic coefficients are effective in the classification and recognition of different behavioral acoustic signals with interspecific acoustic signals of P. vannamei . Meanwhile, the SVM classifier based on OvR classification strategy can model the acoustic signal characteristics of different underwater biological behaviors more efficiently and has classification accuracy as high as 93%.

Identification of long non-coding RNA p34822 as a potential plasma biomarker for the diagnosis of hepatocellular carcinoma - Cheng Wang; Tianyu Ren; Keyu Wang; Shaogeng Zhang; Shubin Liu; Hu Chen; Penghui Yang (Science China Life Sciences, 2017)

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)